Diagnostic and prognostic value of circulating circRNAs in cancer - Wang, Mina (2021)
Cancer has been regarded as one of the leading causes of mortality worldwide. Diagnostic and prognostic biomarkers with high sensitivity and specificity for cancer play a crucial role in preventing or treating cancer. Circular RNAs (circRNAs), which hold great potential for the management of cancer patients due to their abundance, stable property, and high specificity in serum, plasma, and other body fluids, can be used as non-invasive and blood-based biomarkers in cancer diagnosis and prognosis. There are four types of circRNAs including exonic circRNAs (ecircRNA), intronic circRNAs, exon-intron circRNAs (EIciRNA), and intergenic circRNAs. CircRNAs can act as miRNA sponges, affect protein translation, interplay with RNA binding proteins, regulate protein recruitment, and modulate protein scaffolding and assembly. Therefore, the multifunctionalities of circRNAs make them ideal for detecting and predicting cancer. Indeed, circRNAs manifest high sensitivity and specificity in more than ten types of cancer. This review aims to consolidate the types and functions of circRNAs, as well as discuss the diagnostic and prognostic value of circulating circRNAs in cancer.